Menstruation Dysregulation and Endometriosis Development - Kuan, Kevin K. W.; Gibson, Douglas A.; Whitaker, Lucy H. R.; Horne, Andrew W. (Frontiers in Reproductive Health, 2021)
Endometriosis is a common gynecological condition characterized by the growth of endometrial-like tissue outside of the uterus which may cause symptoms such as chronic pelvic pain or subfertility. Several surgical and medical therapies are available to manage symptoms, but a cure has yet to be determined which can be attributed to the incomplete understanding of disease pathogenesis. Sampson’s theory of retrograde menstruation is a widely accepted theory describing how shed endometrial tissue can enter the peritoneal cavity, but other factors are likely at play to facilitate the establishment of endometriosis lesions. This review summarizes literature that has explored how dysregulation of menstruation can contribute to the pathogenesis of endometriosis such as dysregulation of inflammatory mediators, aberrant endometrial matrix metalloproteinase expression, hypoxic stress, and reduced apoptosis. Overall, many of these factors have overlapping pathways which can prolong the survival of shed endometrial debris, increase tissue migration, and facilitate implantation of endometrial tissue at ectopic sites. Moreover, some of these changes are also implicated in abnormal uterine bleeding and endometrial diseases. More research is needed to better understand the underlying mechanisms driving dysregulation of menstruation in endometriosis specifically and identifying specific pathways could introduce new treatment targets. Analysing menstrual fluid from women with endometriosis for inflammatory markers and other biomarkers may also be beneficial for earlier diagnosis and disease staging.